Transformações na cultura drag queen brasileira : reconhecimento da brasilidade em videoclipes da cultura pop - Amaral, Ayrton Senna Seraphim do (2020)
The dissertation investigated the artistic scene and contemporary professional performance of Brazilian drag queens. They were crossed by mediatization processes in the construction of drag queen subjects in the forms of expression of this art. Such transformations expanded the possibilities of being drag and we observed the entry of this marginalized art in the phonographic industry and in pop culture. We aim to analyze the transformations of contemporary drag culture through the mediatization of this art and to verify the presence of brands of Brazilian culture in the video clips of drag queens from Brazil. Thus, we seek to describe the mediatization of contemporary drag culture; check transmedia crossings in the drag queen subject; observe the importance of the video clip for the incorporation of drag culture in pop culture and analyze video clips of drag queens from Brazil in search of elements that demarcate Brazilian culture. We also aimed to investigate how drag queens recognize themselves as Brazilians, resisting a colonizing drag aesthetic spread through current globalized cultural products. We made the construction of a history of the art of transforming in Brazil and with that we verified that this art went through a process of erasing its Brazilianness. In search of an international artistic projection, the substitution of the national term transformismo, founded by the pioneer Rogéria, was replaced by the word drag queen, contradicting decolonial trends. The case study methodology was used to verify the transformations of the careers of Brazilian drag queens crossed by mediatization processes, being sent to a universe incorporated to the transmedia narrative. We selected three drags from different regions of the country in order to bring a broader sample of national cultural aspects, with Pabllo Vittar as representative of the Northeast, Gloria Groove for the Southeast and Sarah Mitch as the representative of the Midwest. To analyze the video clips and the presence of elements of Brazilianness in the national drag culture, we applied the media analysis methodology for video clips in six structured steps. The analysis of the video clips also conceived the performance concept as a methodological look that went through the mentioned methodological procedures. As results achieved, it was verified the growing power and influence of digital media in the construction of today's drag identities and, finally, analyzed if the video clip is currently a prominent process in the promotion of drag culture incorporating it into pop culture. In this way it was possible to find out how they bring markers of Brazilian cultural elements and negotiate with Brazilian clichés in a positive way, of pride and appreciation of national culture through their mediatized careers. Thus, the research fulfilled its objectives of analyzing the transformations that the drag culture has been experiencing in this broad process of mediatization of the arts and of life. Although issues related to coloniality have emerged as agents that interfere with being and making drag queen in Brazil, such observation was pertinent and important so that we could aim at investigating video clips as media products of drag performance in search of elements of Brazilian culture and recognition Brazilianity in the analyzed drag queens. Because of this, we believe that achievements obtained in the mediatization processes that cross the drag culture collaborate with the insertion of drag culture in pop culture, which, in turn, is able to boost the visibility and consumption of drag queen art in the country.